The antibiotic susceptibility patterns of uropathogens isolated in Qassim, Saudi Arabia‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬ - Osama Al Wutayd; Abdullah Al Nafeesah; Ishag Adam; Ibrahim Babikir (Journal of Infection in Developing Countries)
Introduction: Antimicrobial resistance is a global health problem. The present study was carried out to determine the prevalence and antibiotic resistance of uropathogens in the outpatient departments (OPDs) at the clinics of Qassim University, Saudi Arabia.